Facilitating Evaluation to Lead Meaningful Change. Issue 149 (March 2016) - Catsambas, Tessie Tzavaras
Abstract: Evaluation education and training has traditionally emphasized methodological skills and ignored soft skills. A review of routine evaluation tasks, however, reveals that evaluation typically requires the evaluator to work with groups of people for organizing and managing an evaluation, as well as in collecting and analyzing data; that is, evaluators must frequently facilitate group interactions to conclude an evaluation successfully. A juxtaposition of evaluator and facilitator competencies shows significant overlap between them. Furthermore, evaluations of increasing complexity call for higher levels of facilitation. Transformational evaluations call for significant self‐development and strengthening of leadership competencies. Through development and use of facilitation tools and techniques, facilitation can be used to enhance the effectiveness and use of an evaluation.